General banking activities of Janata Bank Limited: a study on Mohakhali corporate branch, Dhaka. - Hossain, Khandaker Junaed (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.